2022
DOI: 10.1002/cjp2.289
|View full text |Cite
|
Sign up to set email alerts
|

Identification and therapeutic evaluation of ALK rearrangements in non‐small‐cell lung cancer

Abstract: This study aimed to present a comprehensive assessment of anaplastic lymphoma kinase (ALK) rearrangements evaluated by DNA/RNA-based next-generation sequencing (NGS) and Ventana immunohistochemistry (IHC) in patients with non-small-cell lung cancer (NSCLC) and to evaluate the therapeutic outcomes of ALK tyrosine kinase inhibitor (TKI) treatment. We investigated ALK gene fusions in 14,894 patients with NSCLC using Ventana IHC and NGS, including 12,533 cases detected via DNA-based NGS and 2,361 cases using RNA-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…The percentage distribution of specific fusion partners was similar to the results of other studies. It is noteworthy that in one case where the FAM114A1-ALK variant was detected, it was not confirmed by any of the other methods (FISH, IHC, or RT-PCR) [6]. The results showed that only the NGS method could detect all partners of the ALK gene and all their variants, and perhaps in the future, it should become the gold standard in diagnosis of ALK gene rearrangement.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The percentage distribution of specific fusion partners was similar to the results of other studies. It is noteworthy that in one case where the FAM114A1-ALK variant was detected, it was not confirmed by any of the other methods (FISH, IHC, or RT-PCR) [6]. The results showed that only the NGS method could detect all partners of the ALK gene and all their variants, and perhaps in the future, it should become the gold standard in diagnosis of ALK gene rearrangement.…”
Section: Discussionmentioning
confidence: 87%
“…FISH failed to detect EIF2AK3-ALK, PRKAR1A-ALK, and one of the EML4-ALK variants [5]. In 2022, Zhao et al [6] tested nearly 15000 patients using the NGS and IHC methods, including 12533 cases examined by DNA-based NGS and 2361 cases examined by RNA-based NGS tests. Based on DNA examination, they showed the presence of ALK gene rearrangements in 439 (3.5%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant ALK expression (i.e., rearrangement negative) has been described in lung neuroendocrine carcinomas (including small cell lung carcinomas) and neural tissue ( 22 , 55 ). Because ALK IHC is a standalone test, reviewing the H&E before scoring the ALK IHC slide is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…NGS should be performed using a clinically validated NGS panel, which ideally should include all guideline recommended biomarkers for patients with advanced NSCLC ( 6 , 7 ). Although there are no recent head-to-head comparisons of all the main available platforms using a large cohort of real-world ALK positive patients, most NGS panels should theoretically have a high performance for the detection of ALK fusions ( 21 , 22 , 29 ). From a pragmatic stand-point some comments are useful when assessing NGS options or discussing their results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation